Implementasi Perpustakaan Digital Berbasis Web Untuk Peningkatan Layanan dan Minat Baca di MTsN Kota Blitar - Aini, Aini Mahfudhoh; Imam Junaris (Jurnal Pengabdian Masyarakat Nusantara, 2025)
This study aims to describe the implementation of a web-based digital library at MTsN 1 Kota Blitar in improving services and students' interest in reading. The main issues behind this study are the low interest in reading and limited access to conventional library services in the digital era. The study used the Participatory Action Research (PAR) method, involving teachers, librarians, and students. Data were collected through interviews, observations, documentation, and literature studies. The results showed that the optimization of the digital library increased the number of visits, the use of e-book collections, and student involvement in literacy activities. The mentoring program, training in the use of the system, and the active role of “Pustakawan Kecil” contributed positively to strengthening the culture of reading. The implementation of digital libraries not only improves service quality but also builds collective awareness among madrasah residents about the importance of digital literacy. These findings confirm that library digitization is an effective strategy to address the challenge of low reading interest while supporting the creation of an adaptive learning ecosystem in the modern era